Trends of drug expenditure in Taiwan National Health Insurance before and during COVID-19 pandemic - Wu, Shu-I; Lee, An-Sheng; Chung, Ching-Hu (Frontiers in Medicine, 2024)
Background The Taiwanese government adopted the National Health Insurance (NHI) system in March 1995. This study aimed to understand the difference in medication costs before (year 2019) and during the COVID-19 pandemic (2020–2021) among different hospitals for treating their patients. Methods The NHI claims database consisting of claims of prescription drugs for inpatients (IPD) and outpatients (OPD) in Taiwan was used to determine drug expenditure in different hospitals, particularly the top 10 prescription Anatomical Therapeutic Chemical (ATC) categories. Results In medical centers, L01X (other antineoplastic agents) showed the highest drug expenditure, followed by L04A (immunosuppressants) and J05A (direct-acting antivirals). The drug expenditure pattern in regional hospitals was similar to that in medical centers, with L01X (other antineoplastic agents) showing the highest drug expenditure. L01X (other antineoplastic agents) also showed the highest drug expenditure in district hospitals, followed by N05A (antipsychotics) and A10B (blood glucose-lowering drugs, excluding insulin). In clinics, A10B (blood glucose-lowering drugs, excluding insulin) showed the highest drug expenditure. The total medication costs in 2021 were lower or similar to those in 2019. The use of systemic use anti-infectives decreased over time in OPDs among all hospita1 levels but increased in IPDs in medical centers and district hospitals. Furthermore, our analysis revealed that the trend in drug expenditure closely mirrored the trend in drug prescription volume for the highest annual sum cost item among the top 10 drug subgroups across different hospital levels. Conclusion Our analysis found that annual drug expenditures in 2021 were lower or similar to those in 2019, suggesting that the COVID-19 pandemic has contributed to this reduction in drug expenditure.